Decreasing Stereotypy Using NCR and DRO With Functionally Matched Stimulation: Effects on Targeted and Non-Targeted Stereotypy. (January 2017) - Rapp, John T.; Cook, Jennifer L.; McHugh, Catherine; Mann, Kathryn R.
We conducted a series of studies on multiple forms of repetitive behavior displayed by four children with autism spectrum disorder. Study 1 showed that each participant's highest probability repetitive behavior persisted in the absence of social consequences, thereby meeting the functional definition of stereotypy. Study 2 showed that preferred, structurally matched stimulation decreased each participant's targeted (highest probability) stereotypy, as well as their non-targeted (lower probability) stereotypy. Study 3 showed that for three participants, non-contingent access to preferred stimulation decreased immediate and, to some extent, subsequent engagement in targeted and non-targeted stereotypy. For the fourth participant, non-contingent access to preferred stimulation decreased immediate engagement in the targeted stereotypy, but increased subsequent engagement in non-targeted stereotypy; this subsequent increase was attenuated by reducing the duration of access to the preferred stimulus. Study 4 showed that a trial-based differential reinforcement of other behavior (DRO) procedure systematically increased the period of time for which the targeted stereotypy was not displayed for three of three participants. In addition, results showed that the participants' non-targeted stereotypy either decreased or was unchanged when DRO was provided for the targeted stereotypy.